Building a glocal community with a shared future for mankind: smart cities and subnational cooperation, under the legal dimension of twinning towns relations - Manzo, Romina Soledad (2025)
This article reflects on the projection of intercultural policies for development 62, with particular emphasis on the promotion of twinning town relations as appropriate instruments of cooperation to strengthen human capital, foster sustainable development, and deepen the strategic partnership between the People’s Republic of China and the Argentine Republic. It examines the normative and doctrinal framework underpinning these policies and proposes a comparative analysis between Hangzhou’s Future Sci-Tech City (with its Dream Town) and the innovation ecosystem developed in Argentina by the Mar del Plata Information and Communication Technology Association (ATICMA). It also analyzes the various subnational twinning agreements concluded in recent years across Argentina’s main regions. Through this study, it is argued that the projection of intercultural policies aimed at sustainable development requires the articulation of legal norms, principles of international cooperation, sustainable urbanization plans, and concrete actions of technological and cultural exchange, in order to ensure a comprehensive strategic partnership of mutual benefit and intergenerational significance.